The theory of electron states on the dynamically deformed adsorbed surface of a solid - Peleshchak, R.M.; Seneta, M.Ya. (Condensed Matter Physics, 2018)
Dispersion relations for the spectra of surface electron states on a dynamically deformed adsorbed surface of a monocrystal with the Zinc blende structure are received. It is established that the dependences of the band gap width and of the concentration of electrons on the concentration of adatoms N0d upon the solid surface are of nonmonotonous character